DEVELOPING SPEAKING SKILL OF GRADE VIII STUDENTS AT SMP NEGERI 1 PALU THROUGH INTERVIEW - Hijrah Syam; M. Tamrin AM. S. Pettawali (Datokarama English Education Journal, 2021)
This research aims at developing Speaking Skill through Interview. Its method was quasi-experimental research non-equivalent control group design. Its population was the students of grade VIII at SMP Negeri 1 Palu, in which consists of thirteen parallel classes. The experimental class consists of 29 students and control class consists of 30 students. It was done in eight meetings. The variables of this research were speaking skill and interview. The samples of this research were students of grade VIII C and VIII D, selected through cluster sampling technique. Its results indicate that the application of interview has overcome the students’ problem. After analyzing them, the result of t-counted was 10.01. By applying degree of freedom (df) 57(29+30-2), and the level significant 0.05, the value of t-table was 2.00. So, the value of t-counted was higher than t-table. It means that the hypothesis of this research was accepted. Thus, the interview can be applied to develop speaking skill of students grade VIII at SMP Negeri 1 Palu.